Sport and humanism. Organizational models and forms of University sport – in Croatia and Slovenia - Gošnik, Jelka; Kürner, Darja (2013)
In June 1999, higher education ministers from twenty-nine European countries, including Slovenia, gathered in Bologna to sign the Bologna Declaration outlining the course of development in the European higher education system until 2010 Tuning Educational Structures in Europe started in 2000. This is to link the political objectives of the Bologna Process, and at a later stage, the Lisbon Strategy to the higher education. This movement has developed into a constant process to re-designing, re-develop, re-implement, re- evaluate and enhance higher quality degree programmes. The Bologna Process is a political decision to converge the different national systems in Europe. For higher education institutions, these reforms create the platform for discussion of the comparability of curricula in terms of structures, programmes, and delivery. The main aim of the Bologna Process is to allow more opportunities for students and staff in European and international higher education institutions to cooperate and exchange. The Bologna process is named after the Bologna Declaration, which was signed in the Italian city of Bologna on 19 June 1999 by 29 European ministers in charge of higher education. Today, there are 47 countries altogether in the European Cultural Convention and committed to the goals of the European Higher Education. As part of the Tuning Project, a methodology has been designed to understand curricular and make it comparable. First, reference points for generic and subject specific competences are created. In addition, a European Credit Transfer System (ECTS) has been developed as an accumulation system by linking credits to learning outcomes.
Projekt MZOS
ENG